Absence of biopolymers in surface waters inhibits flocs growth in winter: A secret of coagulation over decades. (15th November 2022) - Su, Zhaoyang; Wu, Xiaoting; Yu, Wenbao; Liu, Ting; Li, Xing; Liu, Muyang; Yu, Wenzheng
Abstract: Factors responsible for undesirable coagulation performance in winter have not been well understood by far. The aim of this work is to identify the critical factor(s) and to provide applicable suggestions for drinking water production under low temperature. Specifically, water samples were collected from the river Jingmi (JM), a major drinking water source of Beijing City (China), for a series of coagulation tests. Coagulation processes influenced by factors, including particles and organic matter (natural biopolymers and humics) which commonly present in surface waters, were investigated. A photometric dispersion analyzer (PDA) was employed to reveal flocs formation and their properties impacted by water temperature, ranging from 5 °C to 25 °C. Results showed that the absence of natural biopolymers (40–90 kDa, identified as mixtures of proteins and polysaccharides) in surface water in winter significantly hindered flocs growth at low temperature; flocs size and growth rate continuously improved with artificially increasing concentration of biopolymers with/without particulates (kaolin particles in this study), demonstrating positive roles of biopolymers in coagulating kaolinite/organic water. Nanoscale observation on flocs using scanning electron microscope (SEM) demonstrated a bridging capability of biopolymers in aggregating primary particles into larger clusters, and this facilitated flocs growth at low temperature. The findings of this work are expected to improve the understanding of coagulation mechanisms under low temperature, also contributing to better management of coagulation when purifying surface water during winter months. Graphical abstract: Image 1 Highlights: In winter, lacking biopolymers cause undesired coagulation performance. Biopolymers significantly shortened the time for flocs formation in cold water. Polysaccharide was beneficial for enhancing flocs formation at low temperature. The size of nano-aggregates was mostly greater at low temperature. Biopolymers increased nano-aggregates size at low and normal temperature.